WOMEN’S CHALLENGES ON INCREASING ENTREPRENEURSHIP AND ECONOMIC BENEFIT IN INDONESIA: A LITERATURE REVIEW - Pesta Damayanti; Ritha F. Dalimunthe; Prihatin Lumbanraja (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
In carrying out financial planning, a woman has a very strategic role in the family. Meanwhile, women's interest in entrepreneurship is increasing due to the resources they have, availability of labor, advances in information technology, and easy access to simple technological equipment. This research aims to observe that women have the ability to play roles in daily life and become entrepreneurs and explore the challenges faced in carrying out the role of women in the entrepreneurial field where their role makes a positive contribution to the Indonesian economy. The methodology used in research is using descriptive qualitative, where researchers rely on various literature to obtain research data and use a qualitative approach because the data produced is in the form of words or descriptions.